Preparation of carbon nanotubes with hybrids nanostructure materials. - Martínez , María Laura; Juárez , Juliana María; Gómez Costa, Marcos Bruno; Beltramone, Andrea Raquel; Juárez , Juliana María (Universidad Tecnológica Nacional., 2017)
Carbon nanotubes (CNT's) are allotropes carbon, like diamond, graphite and fullerenes. There are different types of CNT's, depending on the type of the graphite layers, it can be single wall carbon nanotubes (SWCNT's) and multi wall carbon nanotubes (MWCNT's). These nanomaterials show good physical properties such as their density, strength and thermal conductivity. The controllable synthesis of materials with the desired structure and dimensionality is of great significance in material science. In this work, the hierarchical carbon nanotubes (CNTs) were synthesized via a simple chemical conversion route by using Carbon Substrate/Fe3O4-SBA-15 hybrid (all in one). The synthesis of Carbon Substrate/Fe3O4-SBA-15 hybrid was carried out using Fe3O4- SBA-15 as a hard template and sucrose as carbon precursor. Sucrose was dissolved in a solution of H2SO4 in water and to this solution, Fe3O4-SBA-15 was added. The resulting mixture was dried at 373 K and then heated at 433 K for 6 h. A second impregnation was performed in order to ensure the filling of the template pores with the carbon precursor. To obtain the carbon nanotubes, the sample was placed in muffle at 1173 K under nitrogen flow (20mL/min) for 30 min. In order to remove the silica, the material was placed in an HF solution. The CNTs was filtered, washed and dried at 323 K. In the present work, we report the synthesis and characterization of CNTs materials of hybrid material. The material was characterized by X-ray diffraction (XRD) and the morphologies and structural features of the prepared materials were observed from the SEM and TEM images.
Keywords: CNTs; Hybrid materials; Nano estructured materials